2017
DOI: 10.1111/joim.12629
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochlorothiazide use is strongly associated with risk of lip cancer

Abstract: Hydrochlorothiazide use is strongly associated with an increased risk of lip cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
125
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(142 citation statements)
references
References 34 publications
10
125
1
6
Order By: Relevance
“…Results of previous studies of ADs and the risk of skin cancer have been inconsistent . While some have shown increased risk with the use of potassium‐sparing and combination diuretics, but not loop or thiazide diuretics, several studies, including one at KPNC, have shown a significant association between thiazide diuretic use and increased SCC risk . ACE inhibitors and ARBs have been associated with a reduced risk of keratinocyte cancers in some studies and an increased risk in others .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of previous studies of ADs and the risk of skin cancer have been inconsistent . While some have shown increased risk with the use of potassium‐sparing and combination diuretics, but not loop or thiazide diuretics, several studies, including one at KPNC, have shown a significant association between thiazide diuretic use and increased SCC risk . ACE inhibitors and ARBs have been associated with a reduced risk of keratinocyte cancers in some studies and an increased risk in others .…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological data on the association between photosensitizing drug use and cSCC risk remain limited. Photosensitizing ADs have been associated with lip cancers, the majority of which are mucosal squamous cell carcinomas (SCCs) . However, whether photosensitizing AD use affects cSCC risk is unclear.…”
mentioning
confidence: 99%
“…Alcohol use may also act synergistically with tobacco abuse in lip cancers, although an exact risk exposure value is not known . More recently, HCTZ use has been associated with lip cancers with an odds ratio of 2.1 (95% confidence interval (CI): 1.7–2.6), increasing to 3.9 (95% CI, 3.0–4.9) for high use (≥25 000 mg) . In our series, 20 cutaneous perioral patients (17.2%) and 10 vermilion lip patients (22.2%) were taking HCTZ at the time of MMS.…”
Section: Discussionmentioning
confidence: 66%
“…The first matched 633 patients with squamous cell carcinoma (SCC) of the lip with 63 067 population controls 2. The second was a study of 71 533 patients with basal cell carcinoma (BCC) and 8629 case patients with SCC who were matched with 1 430 883 and 172 462 population controls, respectively 3. People exposed to the highest cumulative dose of hydrochlorothiazide (≥200 000 mg) were at increased risk of BCC (adjusted OR 1.54, 95% CI 1.38 to 1.71) and SCC (OR 7.38, 95% CI 6.32 to 8.60).…”
Section: Overviewmentioning
confidence: 99%